Risk factors of neonatal mortality in Jember Regency, Indonesia: A case-control study - Alvianto, Muhammad Azirul Afif; Kusumawardani, Devi Arine; Baroya, Ni'mal (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Neonatal mortality constitutes most infant deaths in Indonesia, influenced by maternal and infant factors, smoking exposure levels during pregnancy, and the seeking of health services. Objectives: The study aimed to determine risk factors associated with neonatal mortality in Jember Regency. Methods: This observational analytical study employed a case-control design, with 42 cases and 42 controls selected by simple random sampling. Data collection used a documentation study to obtain maternal and infant characteristics, and maternal cigarette smoke exposure level was assessed using a direct interview SHSES questionnaire. Results: Mostly the age of mothers from case and control 20-35 years, gestational age 37-42 weeks, upper arm circumference ≥23.5 cm, not anemic, parity 2-4, experiencing complications, heavy exposure to cigarette smoke, birth spacing 24-60 months, birth weight <2500 & >4000 grams, inappropriate ANC, delivery assisted by health workers in health care facilities, and using the abdominal delivery method. Preterm and postterm delivery increased neonatal death risk 3.5 times (OR =3.511; 95% CI = 1.316-9.364), maternal or infant complications increased risk 4.2 times (OR = 4.200; 95% CI = 2.445-7.214), extreme birth weight increased risk 4.4 times (OR = 4.462; 95% CI = 1.785-11.154), and the vaginal delivery method is 0.194 times (OR = 0.194; 95% CI = 0.073-0.518) more protective than the abdominal delivery method. Conclusions: Preterm and post-term birth, maternal and neonatal complications, extreme birth weight, and abdominal delivery were associated with neonatal mortality. Strengthening early risk detection and antenatal care quality to prevent complications, optimize birth outcomes, and improve referral coordination to support targeted neonatal mortality reduction strategies.